Alternative control of gastrointestinal worms in cattle: Nematophagous fungi and herbal medicines - Neto, Luiz Felipe Gonçalves Amaral; Oliveira, Karine Hellen Carvalho de; Alves, Marcio Luiz de Pinho; Arruda, Ana Carolina de Castro; Silva, Luane Ellen Lopes da; Bezerra, Stefane Santos; Sena, Maria Eduarda do Nascimento; Uchôa, Alessandra dos Reis (Seven Editora, 2023)
Cattle farming is of paramount importance to the national economy, being represented by 214 million animals. Helminths are a major obstacle to animal production and represent one third of the parasitic diseases that affect cattle. The main form of control of this pathology is from the use of chemotherapy drugs, however, the easy access of the producer to anthelmintics, combined with the lack of adequate professional guidance, has led to the indiscriminate use of these drugs and, consequently, the increase of parasitic resistance. Due to this growth, the emergence of promising alternative control strategies for worms has been observed, such as biological control using nematophagous fungi, as well as the use of herbal medicines. DOI:https://doi.org/10.56238/ptoketheeducati-085